(untitled) (Journal of the College of Basic Education, 2024)
This study aims at investigating the role of using Artificial Intelligence Murf Application for promoting speaking skill of Iraqi EFL college students. To achieve the aim of the present study, the following hypothesis has been put: There is no statistically significant differences at (á≤0.05) between the mean scores of the experimental group who is taught speaking skill according to Artificial Intelligence Murf Application and that of the control group who is taught according to the traditional way in the post-test .Thus , an experiment design was adopted . The sample of the study was Purposive sample consisted of 68 students from 3rd year class English department college of basic education University of Diyala , (35) students as an experimental group which are taught speaking skill by the use of Artificial Intelligence Murf Application and (33) students as a control group which are taught according to the traditional way during the academic year (2022 -2023). Meanwhile, the subjects of both groups are matched according to their age, level of parents’ education, and their scores in the pre-test. Pre-test and post-test have been designed and the validity of the tests and the lesson plans have been obtained by exposing them to jury members in the fields of EFL and linguistics. The data was collected, coded out and analyzed by using independent T-Test, two-way ANOVA and paired T-Test to answer the questions of the study. The researcher design (10) tutorials, e-learning content by using Murf application , that the user only needs to write the text, select the voice and language, and Murf AI takes care of the rest. , which aimed at training the experimental group how to speak fluently by using the Artificial Intelligence Murf Application . The control group , on the other hand was taught the same material through using the traditional way. The reliability of the tests has been secured by using Alfa Cronbach formula found to be (0.86) which indicates high reliability . Statistical analysis of data achieved through using the t-test indicates that there are statistically significant differences between the mean scores of the two groups in favour of the experimental group in the post test . The researcher concludes that using Artificial Intelligence Murf Application develops students’ speaking skill and provides them with opportunities to actively develop their performance , and helps find out what a student does and does not know, building a personalized study schedule for each learner considering the knowledge gaps. In such a way, AI tailors studies according to student’s specific needs, increasing their efficiency. and the researcher suggests to use it to make another study for other stages and other subjects.